Development of Learning Tools with the Application of Learning Inventions to Improve Mathematical Problem Solving Ability Social Arithmetic Material - Ningsih, Fadriati; Murni, Atma; Roza, Yenita (FKIP-Universitas Riau, 2020)
The results of the preliminary study indicate that the learning tools used by the teacher do not meet the 2013 curriculum rules. This study aims to produce learning tools with the application of discovery learning to improve Mathematical Problem Solving Ability (KPMM) on social arithmetic materials for grade VII junior high school. This study used the Borg and Gall development model with stages: (1) research and data collection; (2) planning; (3) development of learning tools; (4) limited trials; (5) product revisions; (6) field trials; (7) product revisions; (8) final product test; (9) revision of the final product; and (10) dissemination and implementation. The validation results showed that it was very valid with consecutive average percentages for KPMM problems that were 94.64%, syllabus was 90.10%, RPP was 93.14%, and LKPD was92.60%. In the final product test phase, learning tools wereused through pre-experimental research to see the increase in KPMM. The final product test results indicated that there was an increase in KPMM of students using learning tools. This means that the learning tool with the application of discovery learning in social arithmetic material in class VII SMP has been valid, practical, and effective.